2016
DOI: 10.1038/nmat4588
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymer structure and revisited hydrogen evolution catalytic mechanism for amorphous molybdenum sulfide

Abstract: Molybdenum sulfides are very attractive noble-metal free electrocatalysts for the hydrogen evolution reaction (HER) from water. Atomic structure and identity of the catalytically active sites have been well established for crystalline molybdenum disulfide (c-MoS 2 ) but not for amorphous molybdenum sulfide (a-MoS x ) which displays significantly higher HER activity compared to its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

59
591
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(656 citation statements)
references
References 52 publications
59
591
1
5
Order By: Relevance
“…In a recent report, Tran et al have identified the formation of metal hydrides from unsaturated Mo atoms as a key step in the HER mechanism from amorphous MoS x (ref. 48). Our results provide additional insight into the origin of HER activity of molybdenum sulfide catalysts and suggest that amorphous MoS x and MoS 2 nanosheets share a similar mechanism involving unsaturated Mo active sites.…”
mentioning
confidence: 56%
“…In a recent report, Tran et al have identified the formation of metal hydrides from unsaturated Mo atoms as a key step in the HER mechanism from amorphous MoS x (ref. 48). Our results provide additional insight into the origin of HER activity of molybdenum sulfide catalysts and suggest that amorphous MoS x and MoS 2 nanosheets share a similar mechanism involving unsaturated Mo active sites.…”
mentioning
confidence: 56%
“…[1][2][3] Among sustainable energy systems, photoelectrochemical (PEC) splitting water into hydrogen and oxygen is a potential way for solar energy conversion and storage. [1][2][3] Among sustainable energy systems, photoelectrochemical (PEC) splitting water into hydrogen and oxygen is a potential way for solar energy conversion and storage.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Recently, there have been important fi ndings regarding (i) the use of amorphous molybdenum sulfi de (a-MoS x ) catalysts for HER [10][11][12][13][14] which exhibits signifi cantly higher HER electrocatalytic activity than its crystalline molybdenum disulfi de [ 15 ] and (ii) the use of Co-based layered double hydroxide for OER due to the formation of catalytic active Co species layer on the surface when driven by electrical energy, [16][17][18][19][20] and (iii) the ability of its layered structure to facilitate the diffusion and proton-coupled electron transfer of electrolytes. [7][8][9] Recently, there have been important fi ndings regarding (i) the use of amorphous molybdenum sulfi de (a-MoS x ) catalysts for HER [10][11][12][13][14] which exhibits signifi cantly higher HER electrocatalytic activity than its crystalline molybdenum disulfi de [ 15 ] and (ii) the use of Co-based layered double hydroxide for OER due to the formation of catalytic active Co species layer on the surface when driven by electrical energy, [16][17][18][19][20] and (iii) the ability of its layered structure to facilitate the diffusion and proton-coupled electron transfer of electrolytes.…”
mentioning
confidence: 99%